2002
DOI: 10.1136/bjo.86.3.316
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic macular oedema: a comparison of vitreous fluorometry, angiography, and retinopathy

Abstract: Aim: To evaluate the relation between the quantitative measurement of vitreous fluorescein with fluorescein angiography and retinopathy in diabetic patients with and without clinically significant macular oedema (CSMO). Methods: In a prospective cross sectional study, passive permeability and active, outward transport of fluorescein across the blood-retinal barrier were quantitated with vitreous fluorometry in 61 eyes from 48 patients with CSMO and 22 fellow eyes without CSMO, after exclusion of eyes with prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 24 publications
4
16
0
4
Order By: Relevance
“…The magnitude of retinal leakage of fluorescein correlates with the severity of retinopathy and visual acuity and is more important in macular oedema (Sander et al 2002). In agreement, in our study, patients with maculopathy had the highest urinary levels of IgG2 and IgG2/IgG4 suggesting a widespread capillary damage with a general change in size selectivity of the basements membrane in the capillaries.…”
Section: Discussionsupporting
confidence: 90%
“…The magnitude of retinal leakage of fluorescein correlates with the severity of retinopathy and visual acuity and is more important in macular oedema (Sander et al 2002). In agreement, in our study, patients with maculopathy had the highest urinary levels of IgG2 and IgG2/IgG4 suggesting a widespread capillary damage with a general change in size selectivity of the basements membrane in the capillaries.…”
Section: Discussionsupporting
confidence: 90%
“…This result indicates that DCE-MRI can detect BRB damage in patients with retinal edema associated with diabetes. Furthermore, these data are consistent with results from previous vitreous fluorophotometry studies that showed significantly greater contrast influx in diabetic patients than in control groups (14)(15)(16). Differences between NCS and CS subgroups that were observed in the vitreous fluorophotometry studies (14)(15)(16) were not found in this study, but this could simply be due to the relatively small sample size of the NCS and CS subgroups.…”
Section: Resultssupporting
confidence: 88%
“…The reasons discussed for the development of persistent macular edema are diverse. Breakdown of the bloodretinal barrier (BRB) and vitreoretinal traction are probably the most relevant factors [25,30].…”
Section: Introductionmentioning
confidence: 99%